Access to rehabilitation services for road traffic injury patients in Namibia. Issue 25 (4th December 2022) - Chatukuta, Mitchel; Groce, Nora; Mindell, Jennifer S.; Kett, Maria
Abstract: Purpose: Road traffic injuries (RTIs) are a major public health issue worldwide. The importance of physical rehabilitation following RTI is well documented. However, globally there has been very little research on the accessibility of rehabilitation services following road injury. Namibia is one of the five African countries with a fuel tax levy fund (Motor Vehicle Accident Fund, MVAF), a system of case managers, medical care, and case management system for coordination of long-term care. Materials and methods: We investigated the availability of physical rehabilitation services to RTI injured in Namibia, through interviews with RTI patients and health care workers. Results: Unlike the few other studies done in Sub-Saharan Africa (SSA), most RTI injured individuals in Namibia report they are able to access some rehabilitation following injury. In large measure, this is due to the effective MVAF system which they felt ensures follow up care for many after having an RTI. However, we found that access to rehabilitation is skewed in favour of those living in Windhoek and other urban areas compared with those in non-urban areas. Conclusions: The MVAF model seems to enhance access to rehabilitation and is a model which could be replicated in other SSA countries and other low and middle income countries. Implications for rehabilitation: Road traffic injuries (RTIs) are a major global public health challenge with over 1.2 million people killed and a high burden of disability and Namibia is one of the worst affected countries globally. There is lack of knowledge on the availability to physical rehabilitation following road injury in Namibia. Our study shows the Motor Vehicle Accident Fund (MVAF) model seems to enhance access to rehabilitation and is a model which could be replicated in Sub-Saharan Africa and other low and middle income countries.